The effect of buceng extracts on androgen production in Sprague Dawley male rats (Faculty of Medicine Universitas Indonesia, 2012)
Background: Buceng is a combination of plant of purwoceng (Pimpinella alpina Molk) and pasak bumi (Eurycomalongifolia Jack) that has been traditionally used to enhance adult male vitality. However, the mechanism of action of buceng has not been understood. This study was aimed to elucidate whether buceng could increasing Testosterone (Te), Luteinizing Hormone (LH), and Follicle Stimulating Hormone (FSH) level in rats.Methods: 20 male Sprague Dawley rats were randomly assigned into two groups. After one week of acclimatization, control group was given aquadest 2 mL, while treated group B received 2 mL (containing 25 mg) buceng extract for seven successive days. The plasma concentration of Te, LH, and FSH were assesed by RIA and IRMA method respectively. Independent t-test was used to analyze the different concentration of Te, LH, FSH between the two groups.Results: Testosterone level of treated group was significantly higher (3.55 pg/mL) compared to control group (1.00 pg/mL), p = 0.003. LH concentrations of treated group (0.12 pg/mL) was slightly but not significantly higher compared to control group (0.11 pg/mL), p = 0.810. Likewise, the FSH level was not significantly different between the two groups (0.15 vs 0.14 pg/mL, p = 0.088).Conclusion: Administration of buceng extract increases testosteron level which might play a role in enhancing male vitality. (Med J Indones 2012;21:28-31)Keywords: Eurycomalongifolia Jack, FSH, LH, male vitality, Pimpinella alpina Molk, testosterone